Burden of febrile neutropenia in paediatric oncology: Experience from Children’s Hospital Lahore Pakistan (Journal of Fatima Jinnah Medical University, 2021)
Background: Infection is the major cause of morbidity and mortality in children with cancer. Chemotherapy induced febrile neutropenia-associated mortality is much higher in low-middle-income countries than in high-income countries, emphasizing the need of prevention, early identification and timely management of infection related complications in these children. Objective of this prospective study was to analyze the burden of chemotherapy induced febrile neutropenia and to assess the leading risk factors.Patients and methods: Prospective cohort study was done in 100 patients with febrile neutropenia (fever of 38.3℃ and ANC
Keywords: Chemotherapy; Febrile Neutropenia; Low-Middle-Income country; Health Education